2008
DOI: 10.1016/j.jpeds.2007.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Relationships between Iron Deficiency with or without Anemia and Infant Social-Emotional Behavior

Abstract: Objective-To assess dose-response relations between severity of iron deficiency (ID) and infant social-emotional behavior.Study design-Cohort of 9-to 10-month-old African-American infants (n = 77 with final iron status classification). Infants were provided oral iron for 3 months. Social-emotional outcomes included mother and examiner ratings at 9 and 12 months and quantitative behavioral coding from videotape at 12 months. General linear model analyses tested for linear effects of iron status group (ordered f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
0
12

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(152 citation statements)
references
References 25 publications
4
132
0
12
Order By: Relevance
“…In 1 study [34] , the level of Hb at which motor development was found to decline was 95 g/l. However, in another study [31] , behaviour was found to change in iron-deficient non-anaemic children.…”
Section: Discussion Of Observational Studiesmentioning
confidence: 87%
See 1 more Smart Citation
“…In 1 study [34] , the level of Hb at which motor development was found to decline was 95 g/l. However, in another study [31] , behaviour was found to change in iron-deficient non-anaemic children.…”
Section: Discussion Of Observational Studiesmentioning
confidence: 87%
“…There was no association with 2 memory tests (digit span, block design) and a reading test. The prevalence of IDA was too small to examine relationships with IDA alone.In a recent study, behavioural differences were related to ID in a dose-response way across 3 groups from ironsufficient non-anaemic, to iron-deficient non-anaemic to IDA [31] . The behaviours showing a linear trend included shyness, orientation/engagement, soothability and positive affect.…”
mentioning
confidence: 98%
“…The data collection tool was based on medical references and previous literatures (Al-Alawi F, March 2015;Carter et al, 2010;Hassan et al, 2005;Lozoff et al, 2008;Sherriff A, 2001;Talebi et al, 2012;Williams et al, 1999). The content validity was tested via two pediatric consultants working in Ministry of Health.…”
Section: Data Collection Toolmentioning
confidence: 99%
“…Recent studies have yielded significant association between IDA and poor cognition, school achievement and behavioral problems (Carter et al, 2010;Lozoff et al, 2008;Sherriff, 2001;Williams et al, 1999). However, iron therapy can be accompanied by bothersome side effects that might affect compliance (Talebi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…28,29 However, few studies have been published assessing the impact of prenatal or fetal ID on early child cognitive development. Evidence emanating from randomized controlled trials comparing the cognitive function or behavior of children between pregnant women who had iron (iron and folic acid) supplementation to a placebo or iron and folic acid, to folic acid only treatments are irreconcilable.…”
Section: Figurementioning
confidence: 99%